Pentingnya Pemahaman Importir pada Kegiatan Jasa Titip Barang Impor: Studi Kasus - Intan Sianturia; Rizqi Aini Rakhman; Bugi Nugraha (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the importance of importers' understanding of imported goods entrustment services. The research method used is a qualitative method with a descriptive approach, using structured interviews as a data collection technique. The research results highlight problems that often arise in import activities using goods entrustment services, especially related to the importer's lack of understanding of the applicable regulations, which can result in goods being trapped in the Customs inspection process. The existence of the Deposit Service Company (PJT) is considered quite responsive in responding to this problem by providing solutions or alternatives to facilitate the release of imported goods from Customs. However, there is a mistaken perception that PJT can help with the document and licensing process, even though this completeness should be the responsibility of the importer as the owner of the goods. This research concludes that it is important to better educate importers regarding import regulations, as well as a clear role between importers and PJTs in ensuring compliance with applicable procedures. Keywords: Customs, Import, Deposit Service Company